2022
DOI: 10.1038/s41598-022-15339-8
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the roles of Haspin and VRK1 in histone H3 phosphorylation during mitosis

Abstract: Protein kinases that phosphorylate histones are ideally-placed to influence the behavior of chromosomes during cell division. Indeed, a number of conserved histone phosphorylation events occur prominently during mitosis and meiosis in most eukaryotes, including on histone H3 at threonine-3 (H3T3ph). At least two kinases, Haspin and VRK1 (NHK-1/ballchen in Drosophila), have been proposed to carry out this modification. Phosphorylation of H3 by Haspin has defined roles in mitosis, but the significance of VRK1 ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…S2B and S2C). Because TP53 is mutated in 28% of glioblastoma ( 22 ), we queried whether VRK1 knockdown correlated with TP53 mutation status. We observed no correlation between TP53 mutation status and VRK1 CRISPR score in 79 CCLE cell lines of the central nervous system (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2B and S2C). Because TP53 is mutated in 28% of glioblastoma ( 22 ), we queried whether VRK1 knockdown correlated with TP53 mutation status. We observed no correlation between TP53 mutation status and VRK1 CRISPR score in 79 CCLE cell lines of the central nervous system (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have found that the affinity-purified rabbit polyclonal antibody B8634 selectively binds H3T3ph in vitro and in cells, and that RNAi, inhibition, or CRISPR/Cas9 knockout of the H3T3 kinase Haspin eliminates epitope recognition in cells (Cartwright et al, 2022; Dai et al, 2005; Wang et al, 2012). Using ELISAs on chemically synthesized Histone H3 peptides, we found that the B8634 antibody was indeed specific for H3T3ph, and did not recognize H3S10ph, H3T11ph, or H3T22ph (Figure S1A).…”
Section: Resultsmentioning
confidence: 99%
“…Although there is strong evidence that Haspin is the major H3T3 kinase in mitotic cells (Cartwright et al, 2022; Dai et al, 2005; De Antoni et al, 2012; Markaki et al, 2009; Wang et al, 2012; Zhou et al, 2017), other potential kinases have been proposed (Kang et al, 2007; Karakkat et al, 2019). However, we found that phosphorylation of H3T3 driven by all endogenous kinases active in lysates of mitotic HeLa cells was severely curtailed by H3K4me3 (Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…OPG97 (L3L) is a VACV core component involved in the transcription of early genes. The AlphaFold model of this protein showed significant structural similarity to Ser/Thr proteins kinases, in particular the atypical kinase domain of haspin, an animal chromatin remodeling regulator (26), but the catalytic site residues are partially replaced in the poxvirus protein (Figure 3a). Notably, the aspartate in the active site has not been exchanged for crododilepox virus OPG97 but the lysine at the ATP-binding site is present.…”
Section: Exaptation Of Cellular Proteins For Viral Functionsmentioning
confidence: 99%